Association of Body Mass Index and Postoperative Acute Kidney Injury in Patients Undergoing Laparoscopic Surgery - Argalious, Maged Y. (Ochsner J, 2017)
BACKGROUND: Whether the deleterious effects of carbon dioxide pneumoperitoneum on the kidneys are exacerbated in the obese population remains unknown. We hypothesized that increased body mass index (BMI) is associated with an increased incidence of postoperative acute kidney injury (AKI) in patients undergoing noncardiac laparoscopic surgery. METHODS: Following institutional review board approval, we analyzed data on 8,543 adult patients with American Society of Anesthesiologists physical status scores of I-IV who had inpatient noncardiac laparoscopic surgery from 2005-2014. Because the exposure (current BMI) is a chronic condition, we a priori assumed that diabetes mellitus, hypertension, coronary artery disease, and chronic obstructive pulmonary disease might mediate the effect of obesity on outcome. Our primary analysis was a proportional odds logistic regression model with current BMI as a predictor and AKI as an ordinal outcome. RESULTS: After controlling for potential confounding variables, the odds of developing a more serious level of AKI was 7% (95% CI 0%, 15%) greater with a 5-unit increase in BMI (P=0.05). When the analysis was adjusted for the a priori mediators in an attempt to estimate the pure effect of BMI on AKI, the result was no longer significant (Wald test P=0.35), with the residual effect of BMI of 3% (95% CI –4%, 11%). CONCLUSION: We found a marginal association between BMI and an increased risk of developing AKI in adult patients after having noncardiac laparoscopic surgery. The BMI effect became insignificant when potential mediator variables were considered. The association of BMI and AKI after noncardiac laparoscopic surgery is likely mediated through components of the metabolic syndrome.